2021
DOI: 10.1371/journal.pone.0237278
|View full text |Cite
|
Sign up to set email alerts
|

How predictability affects habituation to novelty

Abstract: One becomes accustomed to repeated exposures, even for a novel event. In the present study, we investigated how predictability affects habituation to novelty by applying a mathematical model of arousal that we previously developed, and through the use of psychophysiological experiments to test the model’s prediction. We formalized habituation to novelty as a decrement in Kullback-Leibler divergence from Bayesian prior to posterior (i.e., information gain) representing arousal evoked from a novel event through … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…10). Our previous study showed that the former represents novelty as a source of arousal potential (Yanagisawa et al, 2019;Ueda et al, 2021). I confirmed that the term also means expectation incongruity and unfamiliarity.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…10). Our previous study showed that the former represents novelty as a source of arousal potential (Yanagisawa et al, 2019;Ueda et al, 2021). I confirmed that the term also means expectation incongruity and unfamiliarity.…”
Section: Discussionsupporting
confidence: 64%
“…In our previous study (Yanagisawa et al, 2019), we defined Bayesian surprise as information gain because it represents information content gained from incoming sensory data. I considered information gain to be an index of novelty and experimentally verified that it corresponds to human surprise (i.e., high arousal emotion) induced by unexpected and novel stimuli (Sekoguchi et al, 2019;Yanagisawa et al, 2019;Miyamoto and Yanagisawa, 2021;Ueda et al, 2021). Information gain refers to information content elicited by incongruity between prior expectation and posterior perception (Friston et al, 2015).…”
Section: Novelty and Uncertaintymentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental studies have shown that collative variables form the Wudnt curve in a variety of fields such as art (Marin et al, 2016;Miyamoto & Yanagisawa, 2021;Silvia, 2005), design (Hekkert et al, 2003;Hung & Chen, 2012), and food science (Giacalone et al, 2014). Yanagisawa et al formulated the emotion arousal caused by collative variables using information-theoretic quantities and the Wudnt curve function as a summation of reward and aversion functions of information quantities (Miyamoto & Yanagisawa, 2021;Ueda et al, 2021;Yanagisawa, 2021;Yanagisawa et al, 2019). Yanagisawa recently suggested that information-theoretic free energy represents a general form of arousal induced by collative variables (Yanagisawa, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The habituation effect has also been modelled within multiarmed bandits, designed for the optimisation of online marketing content and interactive advertisement delivery 43 . Recent studies and models are focused on predictability and novelty 44 , visual learning 45 , or a mathematical model of emotional habituation 46 , to mention a few.…”
Section: Introductionmentioning
confidence: 99%